Educational attainment in the short and long term: was there an advantage to attending faith, private, and selective schools for pupils in the 1980s?. (2nd November 2018) - Sullivan, Alice; Parsons, Samantha; Green, Francis; Wiggins, Richard D.; Ploubidis, George; Huynh, Timmy
ABSTRACT: This paper asks whether private, selective, and faith schools in England and Wales in the 1980s provided an academic advantage to their pupils, both in the short and longer term. Using longitudinal data from the 1970 British Cohort Study, we examine academic outcomes in compulsory schooling and further education, and the highest qualification gained by age 42. School sector differences are substantially attenuated by controlling for prior pupil characteristics. Nevertheless, a residual effect of private, grammar, and secondary modern schooling remains, both in the short and long term, controlling for both pupil and school characteristics. In the case of faith schools, however, the apparent advantage is restricted to the short term once pupil characteristics are controlled. A unique feature of our analysis is that we control for the individual's faith of upbringing, which is important in reducing what could otherwise be seen as a distinctive Catholic school advantage.